Lingkages Between Foreign Direct Investment and its Determinants in Malaysia - Zunaidah Sulong; D. Agus Harjito (Universitas Islam Indonesia, 2005)
This paper addresses the relationship between Foreign Direct Investment (FDI) and its determinants in Malaysia. The annual data for the period of 1970 to 1999 were employed in this study. The OLS regression is used to determine the relationship between FDI and its independent variables. The variables are estimated in the full model (Model I) and different sub-models (Model II, Model III and Model IV). Generally, the results indicate that there are at least four factors that may be used to predict the level of FDI in Malaysia. These variables are inflation rate, gross domestic product (GDP), import, and export are among the main determinants of FDI in Malaysia.Keywords: foreign direct investment, inflation rate, GDP, import, and export